ChemInform Abstract: α‐MsO/TsO/Cl Ketones as Oxidized Alkyne Equivalents: Redox‐Neutral Rhodium(III)‐Catalyzed C—H Activation for the Synthesis of N‐Heterocycles. Issue 32 (24th July 2014) - Yu, Da‐Gang; de Azambuja, Francisco; Glorius, Frank
Abstract: For the first time, α‐pseudohalo and α‐halo ketones are utilized as oxidized alkyne equivalents in Rh(III)‐catalyzed redox‐neutral annulations to efficiently generate diverse N‐heterocycles.